A study on role of neo adjuvant chemotherapy in locally advanced non-metastatic breast cancer - Siddhartha, Thota; Kanchana, B. (International Surgery Journal, 2018)
Background: Nearly 1.7 million new breast cancer cases were diagnosed worldwide in 2012.Breast cancer is the second most common cancer in women worldwide. Globally, breast cancer now represents one in four of all cancers in women. breast cancer has ranked number one cancer among Indian females with age adjusted rate as high as 25.8 per 100,00 women and mortality 12.7 per 100,000 women. Around 90,000 new cases of breast cancer are diagnosed every year in India and majority present as Locally Advanced Breast Cancer (LABC). Neo adjuvant chemotherapy is a commonly used modality for LABC, that gives an upfront systemic therapy in high risk patients with expected micro metastatic burden and also helps in down staging the disease and offering radical cure. Methods: All Locally Advanced Non-Metastatic Breast Carcinoma (T3 N0, T3 N1, T4a, T4b, T4c, Any N2/N3, MO patients who received Neo Adjuvant Chemotherapy and underwent surgery were included. All these patients received 5-Fluorouracil, Adriamycin and Cyclophosphamide (FAC) regime, following therapy patients were offered either Modified Radical Mastectomy or Breast Conservative Surgery with axillary node dissection and Radiotherapy. Results: Complete response was achieved in 20 (66.6%) patients,3 (10%) of the patients had partial response and 7 (23.3%) progressed clinically. Conclusions: Neo adjuvant chemotherapy helped to study response of tumour size to NAC, down stage disease and to convert inoperable cases to resectability.